Penguatan Manajemen Usaha Ayam Petelur Berbasis UMKM–BUMDes dalam Meningkatkan Perekonomian Desa di Kecamatan Pangururan Kabupaten Samosir - Robinhot Gultom; Junika Napitupulu; Jeudi A. T. P. Sianturi; Jon Henri Purba; Toman E. Panggabean; Anton A. P. Sinaga; Sahat P. Remus Silalahi; Rintan br. Saragih; Tiur Rajagukguk; Selamat Siregar; Saur Melianna; Sondang Ni Bulan Marbun (Universitas Methodist Indonesia, 2026)
This community service initiative aims to strengthen the management of laying-hen businesses based on the UMKM-BUMDes (Village-Owned Enterprise) model, thereby boosting the rural economy in Pangururan District, Samosir Regency. The program was motivated by the significant potential of the laying-hen sector—driven by high egg demand—and the need to address persistent challenges such as high feed costs, limited availability of day-old chicks (DOC), capital constraints, disease risks, and logistical issues. Implementation involved providing guidance and mentoring on production, financial, marketing, and human resource management, alongside the application of core management functions: planning, organizing, executing, and controlling. Furthermore, participants were introduced to business development strategies involving digital technology adoption, product quality improvement, innovation, and the strengthening of partnerships with various stakeholders. The results indicate that the synergy between MSMEs and BUMDes has the potential to enhance business management capacity, create jobs, increase community income and Village-Generated Revenue (PADes), and support the realization of a self-reliant, prosperous, and sustainable village.